Speciation, transportation, and pathways of cadmium in soil-rice systems: A review on the environmental implications and remediation approaches for food safety. (November 2021) - Li, Zhanming; Liang, Yi; Hu, Hangwei; Shaheen, Sabry M.; Zhong, Huan; Tack, Filip M.G.; Wu, Mengjie; Li, Yu-Feng; Gao, Yuxi; Rinklebe, Jörg; Zhao, Jiating
Graphical abstract: Highlights: Transportation and pathways of Cd in soil-rice systems have been reviewed. Cd accumulation in rice can be controlled by water, fertilizer and rice variety. Transporters are critical to Cd uptake by rice root through the symplast pathway. Phytoremediation can achieve the aims of green and sustainable remediation of Cd. Low-Cd rice cultivars with modified transporters are expected to avoid Cd uptake. Abstract: Cadmium (Cd) contamination in paddy fields is a serious health concern because of its high toxicity and widespread pollution. Recently, much progress has been made in elucidating the mechanisms involved in Cd uptake, transport, and transformation from paddy soils to rice grains, aiming to mitigate the associated health risk; however, these topics have not been critically reviewed to date. Here, we summarized and reviewed the (1) geochemical distribution and speciation of Cd in soil-rice systems, (2) mobilization, uptake, and transport of Cd from soil to rice grains and the associated health risks, (3) pathways and transformation mechanisms of Cd from soil to rice grains, (4) transporters involved in reducing Cd uptake, transport, and accumulation in rice plants, (5) factors governing Cd bioavailability in paddy, and (6) comparison of remediation approaches for mitigating the environmental and health risks of Cd contamination in paddy fields. Briefly, this review presents the state of the art about the fate of Cd in paddy fields and its transport from soil to grains, contributing to a better understanding of the environmental hazards of Cd in rice ecosystems. Challenges and perspectives for controlling Cd risks in rice are thus raised. The summarized findings in this review may help to develop innovative and applicable methods for controlling Cd accumulation in rice grains and sustainably manage Cd-contaminated paddy fields.